Webster's third new international dictionary of the English language unabridged with seven language dictionary - Gove, Philip Babcock (Merriam-Webster, 1993)
Webster\'s Third New International Dictionary, Unabridged, is the largest, most comprehensive American dictionary available, containing over 472,000 entries, 14,000 new words in a special Addenda Section, 3,000 illustrations, and 140,000 etymologies describing word origins. Boxed hardcover, buckram binding, thumb-notched.
Keywords: Dictionaries as Topic; slovníky jako téma